Le contexte d’écriture, le contexte de lecture et la présence du pictural dans « Le Turquetto » de Metin Arditi - Komandera, Aleksandra (2023)
This paper presents the importance of art in Metin Arditi’s life and work and examines if his novel “Le Turquetto” can be considered an example of pictural writing. First, we present the context of writing and the role of art in the writer’s personal experience. Then, we describe different thematic and formal manifestations of the pictural in his text, based on Liliane Louvel’s typology, to verify how intermedial references between literature and painting influence the reader’s reception.
Keywords: Arditi Metin